Multivariate analysis of milk yield, lactation length and calving interval in female buffaloes - Bezerra Junior, Jailton S.; Silva, Fabiane L.; Hongyu, Kuang; Couto, Alberto G.; Medeiros, Rosália B. N.; Araújo, Filipe C. T.; Lima, Luciano G.; Fraga, Angelina B. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: The global market has an increasing demand for buffalo by-products due to their unique nutritional characteristics. Many buffalo herds lack suitable breeding control programs, hindering the implementation of selection programs. Objective: To evaluate milk production per lactation (MP), lactation length (LL), and calving interval (CI) of a herd of crossbred Murrah buffaloes to support buffalo clustering according to their potential. Methods: Data from 543 lactations between 2002 and 2014 from 105 crossbred Murrah female buffaloes were used. Data were subjected to principal component analysis (PCA) and cluster analysis. Results: The first components (PCs) were responsible for 92.32% of the total variation, of which 61.45 and 30.87% were explained by the first (PC1) and second (PC2) components, respectively. The cluster analysis allowed three female buffalo groups according to their potentials. Conclusion: Buffalo farmers can make decisions on nutritional, reproductive management and cow culling based on grouping.